2021
DOI: 10.1186/s41687-021-00294-1
|View full text |Cite
|
Sign up to set email alerts
|

Content validity and psychometric evaluation of the Functional Assessment of Chronic Illness Therapy-Fatigue scale in patients with chronic lymphocytic leukemia

Abstract: Purpose Fatigue is a prominent symptom in individuals with chronic lymphocytic leukemia (CLL). This work evaluates the content validity and psychometric properties of the Functional Assessment of Chronic Illness Therapy-Fatigue scale (FACIT-Fatigue) in patients with CLL to determine if it is fit for purpose in CLL research. Methods The FACIT-Fatigue yields a 13-item total score from a five-item symptom subscale and an eight-item impact subscale. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…An assessment of structural validity using confirmatory factor analysis (CFA) supported the unidimensionality of the FACIT-F scale. 33 Construct validity, as assessed through the convergent approach, indicated overall good validity. Known-groups validity was supported by differences between groups based on various baseline factors.…”
Section: Symptom Severitymentioning
confidence: 98%
See 4 more Smart Citations
“…An assessment of structural validity using confirmatory factor analysis (CFA) supported the unidimensionality of the FACIT-F scale. 33 Construct validity, as assessed through the convergent approach, indicated overall good validity. Known-groups validity was supported by differences between groups based on various baseline factors.…”
Section: Symptom Severitymentioning
confidence: 98%
“…One study, which assessed the content validity of the FACIT-F scale in 40 patients in the first line or relapsed or refractory chronic lymphocytic leukemia (CLL) setting in the US, found that interviewed patients understood the terminology and agreed with response options. 33 The same study investigated structural validity, construct validity, known-groups validity, and internal consistency using data from a phase III RCT (ASCEND) 34 in 263 patients with relapsed or refractory CLL. An assessment of structural validity using confirmatory factor analysis (CFA) supported the unidimensionality of the FACIT-F scale.…”
Section: Symptom Severitymentioning
confidence: 99%
See 3 more Smart Citations